2020
DOI: 10.1007/s10557-020-06965-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Xuezhitong in Patients with Hypertriglyceridemia: a Multicentre, Randomized, Double-Blind, Double Simulation, Positive Drug and Placebo Parallel Control Study

Abstract: Backgroud Xuezhitong (XZT) is an extract of Allium macrostemon Bunge that has lipid-lowering properties. Objective To evaluate the effects of XZT on lipids in subjects with hypertriglyceridemia (HTG) without severe dyslipidaemia. Methods A total of 358 subjects with HTG were enrolled and randomly assigned to receive XZT (2700 mg daily), xuezhikang (XZK) (1200 mg daily) or placebo. The primary endpoint was the reduction or percent reduction in the TG level over 12 weeks of treatment. Results At the 12-week foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…A total of 12 adverse events were reported in this trial (6 in the placebo group and 6 in the D&G group), but none of them were directly related to the research herbal preparation. Xuezhitong (XZT) capsules can also significantly reduce the TG level with good safety [ 14 ]. In this research, 358 hypertriglyceridemia subjects were enrolled and randomly assigned to receive XZT (2700 mg per day), Xuezhikang (XZK) (1200 mg per day), or placebo.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…A total of 12 adverse events were reported in this trial (6 in the placebo group and 6 in the D&G group), but none of them were directly related to the research herbal preparation. Xuezhitong (XZT) capsules can also significantly reduce the TG level with good safety [ 14 ]. In this research, 358 hypertriglyceridemia subjects were enrolled and randomly assigned to receive XZT (2700 mg per day), Xuezhikang (XZK) (1200 mg per day), or placebo.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…XZK is a traditional Chinese medicine with multiple cardioprotective effective, which contains isoflavones and lovastatin and unsaturated fatty acid. Studies have shown that the effect of XZK in reducing TC and LDL-C levels is equivalent to conventional doses statins, and increasing HDL-C levels ( Xu et al, 2017 ; Jia et al, 2020 ). Our efficacy data were consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Xuezhitong (XZT) is a traditional Chinese medicine that includes Allium macrostemon Bunge , also known as Xie Bai, a plant widely used to treat CVD in China. 89,90 Its antilipidemic mechanism of action is unknown but may be related to reverse cholesterol transport. Through this mechanism, the body eliminates excess cholesterol from non-hepatic peripheral tissues by transporting it to the liver for redistribution or removal through excretion into bile by the gallbladder.…”
Section: Methodsmentioning
confidence: 99%
“…Patients received XZT 2700 mg/day, xuezhikang (XZK) 1200 mg/day, or placebo. 90 XZK is a lipid-lowering drug extracted from fermented yeast rice, contains lovastatin, and may lower LDL-C similarly to low-intensity statins (around 24-27%). 90,92 The primary endpoint of percent TG reduction over 12 weeks was statistically significant with a 30.7% reduction in the XZT group compared to 24% and 11.6% in the XZK and placebo groups, respectively.…”
Section: Methodsmentioning
confidence: 99%